Can Academic Freedom Survive Performance Based Research Funding? - Butler, Petra; Mulgan, Roderick (Victoria University of Wellington Law Review, 2013)
Academic Freedom is a largely under-explored right in the common law. Performance or Output Based Research Funding is a relative new phenomenon in regard to the distribution of Government money. Even though this research funding model has been the subject of educational, sociological and political science research, surprisingly little research has examined the implications for academic freedom. This article attempts to fill that lacuna. It examines the right to academic freedom in the context of New Zealand’s Bill of Rights Act 1990, and whether or not output based research funding is a justifiable limitation on the right to freedom of academia protected by that Act.